2005
DOI: 10.1056/nejmoa051185
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos Exposure, Pleural Mesothelioma, and Serum Osteopontin Levels

Abstract: Serum osteopontin levels can be used to distinguish persons with exposure to asbestos who do not have cancer from those with exposure to asbestos who have pleural mesothelioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
253
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 353 publications
(270 citation statements)
references
References 38 publications
10
253
3
4
Order By: Relevance
“…Moreover, the acquisition of chemoresistance by HA-CD44 interaction could be advantage for MPM cells to protect themselves by anti-cancer agents. These ideas are supported by previous reports which demonstrated MPM to be associated with elevated levels of OPN and HA in the pleural effusion (Thylen et al, 1997;Pass et al, 2005;Grigoriu et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, the acquisition of chemoresistance by HA-CD44 interaction could be advantage for MPM cells to protect themselves by anti-cancer agents. These ideas are supported by previous reports which demonstrated MPM to be associated with elevated levels of OPN and HA in the pleural effusion (Thylen et al, 1997;Pass et al, 2005;Grigoriu et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…For instance, it has been reported that small cell lung cancer cells, myeloma cells, glioma cells and colon cancer cells were protected from apoptosis induced by various anticancer agents when the cells were plated on ECM (Damiano et al, 1999;Sethi et al, 1999;Uhm et al, 1999;Kouniavsky et al, 2002). MPM cells are surrounded by pleural effusion, which contains a variety of ECM including hyaluronate (HA) and osteopontin (OPN) (Thylen et al, 1997;Pass et al, 2005;Grigoriu et al, 2007). The ability to grow in pleural fluid suggests that the MPM cells are capable of surviving and proliferating against apoptosis under the influence of this particular microenvironment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multivariate analysis, SUV greater than 10, stage III and IV disease and nonepithelioid histology were associated with poor survival. (Robinson et al, 2003) and osteopontin (OPN) (Pass et al, 2005) were the subject of a number of investigations presented at the meeting.…”
Section: Imaging Raja Floresmentioning
confidence: 99%
“…In an effort to identify occupational mesothelioma earlier during disease progression, high-risk workers can be screened for abnormal serum osteopontin levels, since this is routinely elevated in mesothelioma. Although serum osteopontin may also be elevated in other forms of cancer, Pass et al demonstrated that serum osteopontin has a 77.7% sensitivity and 85.5% specificity for mesothelioma[10]. Finally, we hope this report will stimulate clinicians to consider the possibility of mesothelioma in cases where lung cancer is coupled with immunosuppression.…”
Section: Discussionmentioning
confidence: 72%